Bytový dům - Deutschová, Martina (Vysoké učení technické v Brně. Fakulta stavební, 2014)
Bakalářská práce „Bytový dům“ řeší výstavbu bytových domů v Brně, v městské části Pisárky, která leží nedaleko centra Brna. Práce navazuje na studii z druhého ročníku, jejímž zadáním byl návrh nadstandardních bytů od užitné plochy 60 m2. Bytový dům je navržen na svažité parcele s původním využitím jako zahrada. Má jedno podzemní a tři nadzemní podlaží. Celkem 8 bytů. Nosnou konstrukci tvoří kombinovaný systém založený na základových pásech a patkách, skelet v suterénu je vystřídán zděným systémem v nadzemních podlažích.

The bachelor´s thesis "Apartment building" deals with the construction of a residential apartment in Brno, in the borough of Pisárky. The bachelor´s thesis is based on architecture study of luxury housing that was created at second year of study. It was recomended at least 60 m2 of usable floor area for the apartements. The apartment building is located on sloping terrain with original use as a garden area. The building has one underground and tree floors and the building has 8 apartments. Building structure is created of skeleton system on underground and wall system on floors. The building structure is placed on concrete column base and grid foundation.
Apartment building
Keywords: Bytový dům; Brno; Pisárky; svažitý terén; nadstandardní bydlení; Porotherm; železobetonový skelet; fitness; zelená střecha; lodžie; výplň zábradlí Perspex; Apartment building; Brno; Pisárky; sloping terrain; luxury housing; Porotherm; skeleton system - reinforced concrete; fintess; green roof; loggia; Perspex